Perceived indoor air quality in naturally ventilated primary schools in the UK: Impact of environmental variables and thermal sensation. (22nd September 2020) - Korsavi, Sepideh Sadat; Montazami, Azadeh; Mumovic, Dejan
Abstract: Indoor air quality (IAQ) in classrooms has a significant impact on children's academic performance, health, and well‐being; therefore, understanding children's perception of IAQ is vital. This study investigates how children's perception of IAQ is affected by environmental variables and thermal sensation. In total, 29 naturally ventilated classrooms in eight UK primary schools were selected and 805 children were surveyed during non‐heating and heating seasons. Results show that air sensation votes (ASVs) are more correlated to CO2 levels than to operative temperatures (Top ) during non‐heating seasons and more correlated to Top than CO2 levels during heating seasons. The impact of Top on ASVs decreases with an increase in CO2 levels, and the effect of CO2 levels on ASVs decreases with increase in Top . The most favorable ASVs are given when children feel "cool" and have "as it is" preference. By keeping CO2  < 1000 ppm and Top within children's thermal comfort band, ASVs are improved by 43%. The study recommends that standards should consider the impact of both temperature and CO2 levels on perceived IAQ. Perception of IAQ also affects children's overall comfort and tiredness levels; however, this influence is more significant on tiredness level than that on overall comfort level.